Implementación de la contabilidad comercial en “Sandrimar Store” del cantón La Troncal, provincia del Cañar, periodo julio a septiembre del 2013 - Barragán Romero, María Cumandá (2015)
The implementation of trade ACCOUNTING "SANDRIMAR STORE" THE CANTON the trunk, province of Cañar, period July to September 2013 was conducted in order to provide their owners a basic accounting tool for the efficient management of the accounting system, and this way to have real information on the financial and economic situation of the company as a basis for proper decision making. It was met the objectives set by collecting vouchers source underpinning the business, accounting records and supporting later were designed to record financial transactions and thus structure the accounting process, the same way the Plan was structured and Manual Accounts that allowed the correct record of economic events, and finally the process of accounting was run from the preparation of the initial inventory to generate the Financial Statements. Upon completion of the investigative work in the shop "SANDRIMAR STORE", it was determined that the lack of implementation of commercial accounting, have prevented financial accounting, accurate and timely information for proper decision-making information to solve this problem an accounting system that will serve as an example for future periods, especially for proper decision-making, this reason it is recommended to continue using it to achieve compliance with their goals and improve their profitability was designed